2023
DOI: 10.3390/diagnostics13061150
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA in Plasma and Serum Indicates Disease Severity and Prognosis in Blunt Trauma Patients

Abstract: Background: Trauma is still a major cause of mortality in people < 50 years of age. Biomarkers are needed to estimate the severity of the condition and the patient outcome. Methods: Cell-free DNA (cfDNA) and further laboratory markers were determined in plasma and serum of 164 patients at time of admission to the emergency room. Among them were 64 patients with severe trauma (Injury Severity Score (ISS) ≥ 16), 51 patients with moderate trauma (ISS < 16) and 49 patients with single fractures (24 femur nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…All these pathologies could theoretically be driven – partly or completely – by immunogenic self-DNA and in fact, all of them have been related to self-DNA in the context of non-COVID-19 pathologies. Using trauma as an example, several prospective observational studies reported elevated concentrations of free cfDNA ( 66 68 , 70 ), or of histone-complexed cfDNA ( 170 ), in the blood of severely injured trauma patients. In all these studies, the cfDNA concentrations correlated with poor clinical outcome ( 66 68 , 70 , 170 ).…”
Section: Evidence From Other Pathologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All these pathologies could theoretically be driven – partly or completely – by immunogenic self-DNA and in fact, all of them have been related to self-DNA in the context of non-COVID-19 pathologies. Using trauma as an example, several prospective observational studies reported elevated concentrations of free cfDNA ( 66 68 , 70 ), or of histone-complexed cfDNA ( 170 ), in the blood of severely injured trauma patients. In all these studies, the cfDNA concentrations correlated with poor clinical outcome ( 66 68 , 70 , 170 ).…”
Section: Evidence From Other Pathologiesmentioning
confidence: 99%
“…Using trauma as an example, several prospective observational studies reported elevated concentrations of free cfDNA ( 66 68 , 70 ), or of histone-complexed cfDNA ( 170 ), in the blood of severely injured trauma patients. In all these studies, the cfDNA concentrations correlated with poor clinical outcome ( 66 68 , 70 , 170 ). The causal role cfDNA in the inflammatory response to trauma was shown by the group of Carl Hauser at Harvard ( 67 , 69 ).…”
Section: Evidence From Other Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NABNs are nanomaterials that recognize danger- and pathogen-associated molecular patterns (DAMPs and PAMPs) that stimulate TLRs, leading to inflammation in chronic disease [ 4 , 5 , 6 ]. DAMPs and PAMPs have been clinically found to be increased in trauma [ 7 , 8 , 9 ], inflammatory disease [ 10 , 11 , 12 , 13 ], and cancer [ 14 , 15 , 16 ]. Cell-free nucleic acids are being used for early disease detection, and high levels of DAMPs and PAMPs have been correlated to lower prognoses in many disease states [ 7 , 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…DAMPs and PAMPs have been clinically found to be increased in trauma [ 7 , 8 , 9 ], inflammatory disease [ 10 , 11 , 12 , 13 ], and cancer [ 14 , 15 , 16 ]. Cell-free nucleic acids are being used for early disease detection, and high levels of DAMPs and PAMPs have been correlated to lower prognoses in many disease states [ 7 , 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. NABNs can reduce TLR overactivation by acting as molecular scavengers that bind nucleic acids and other charged molecules, including DAMPs and PAMPs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%